DNA-Citoliq sistem (DCS): a new liquid base cytology sytem– techinalaspects - Longatto Filho, Adhemar; Namiyama, Gislene; Castelo Filho, Adauto; Viann, Maria Regina; Dôres, Gerson B. das; Taromaru, Eliane (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: DCS is a new liquidbase cytology system for cell collected in UCM. Objective: assess technical aspects of DCS under different protocols. Methods: the first experiment was performed with 144 samples. After cervical scraping with Ayre spatula and endocervical brushing, thesample was immediately smeared on the slide and alcohol fixed. The same brush with residual cells was used to scrap the ectocervical surface andconditioned in a UCM tube. For each case, 4 slides were prepared according to DCS procedures, except the vortexing time (5, 10, 15 and 20 seconds) from protocols 1 to 4. The second experiment was made with 50 samples, with a vortexing time of 30 seconds. Cytological criteria for sample qualitywere: cell distribution (empty areas and clumping), fixation artifacts, cellularity and presence of TZC. Results: on the experiment 1, significant differences were detected between protocols 1 and 4, but not between protocols 2 and 3. Compared to conventional smears, DCS preparations showedlesser empty areas in slides 1 and 4 (p = 0.024 and p = 0.003). No fixation artifacts and high TZC representation were found in protocols 3 and 4. Inthe experiment 2, although not statistically significant, more cases with TZC were seen. No adverse effects were found on Pap staining, cytomorphology or on fixation cells properties. Conclusion: these preliminary results with 20 or 30 seconds vortexing yielded well preserved cytomorphology, with high representation of endocervical cells and better cells distribution, thus leading to a favorable expectative regarding its use in large trials forassessing diagnostic performance.